An improved seismicity picture of the Southern Tyrrhenian area by the use of OBS and land-based networks: the TYDE experiment - F. Frugoni (Annals of Geophysics, 2006)
The problem of large location uncertainties for seismicity occurring in the Southern Tyrrhenian Sea have been partially exceeded during the implementation of the long-term scientific mission of the TYrrhenian Deep sea Experiment (TYDE), which allowed the installation of 14 wide-band Ocean Bottom Seismometers (OBS) and Hydrophones (OBH) in the period December 2000 May 2001 on the sea-bottom floor around the Aeolian and Ustica Islands. Local events recorded at landstations have been observed also on the seismograms of the Ocean Bottom Seismic Network (OBSN). Moreover, some hundreds of low magnitude events, undetected from the land networks, have been recorded. We combined the readings of body wave arrival times from OBS-OBH with those from landstations to localise seismic events. We focused our study on three clusters of events representative of the seismic activity of the area: (i) deep events, (ii) Ustica (iii) NE-Sicily. The analysis of the integrated data set of the seismicity off-shore and on-shore, obtained from the combined land-OBS seismic network (Ustica sequence and Deep events), has improved locations in terms of RMS residuals, azimuthal gap, epicentral and hypocentral errors. Moreover, further classes of events have been analysed: the first one includes some local events that could be located only by integrating single trigger readings from the few available land-stations with the OBSN-data; the second one comprises local events that have been detected only by the OBS-OBH stations. In particular, the last cluster underlines the importance of an OBSN in the Tyrrhenian deep basin to reveal its unknown intense micro-seismicity, permitting to better understand both the tectonic and geodynamic picture of the area.